Formulation of Anti Acne Sheet Mask from Bandotan Leaf Extract (Ageratum conyzoides L.) against Propionibacterium acnes - Ginting, Pricella; Leny, Leny; Hafiz, Ihsanul; Hasibuan, Romauli (Journal of Drug Delivery and Therapeutics, 2021)
Acne can occur due to increased sebum excretion, inflammation of the skin triggered by the bacteria Propionibacterium acnes, Staphylococcus epidermidis, Staphylococcus aureus. The purpose of this study was to determine the formulation of sheet mask preparations of bandotan leaf extract (Ageratum conyzoides L.) in inhibiting the growth of Propionibacterium acnes bacteria. This type of research is an experimental study which include plant identification, making ethanol extract of bandotan leaves, making sheet mask formulations, evaluating the characteristics of the preparation and testing antibacterial activity using disc paper method using Mueller Hinton Agar media. The extract was carried out by maceration using 70% ethanol as a solvent. Testing the effectiveness of antibacterial by measuring the diameter of the inhibition zone, after that the data were analyzed using the One Way ANOVA statistical test. The results of the evaluation of the preparation showed that the preparation was homogenous, with pH ranging from 4.5 to 6.5 and the preparation did not cause irritation on volunteers skin. The results of the inhibition zone measurements showed that the inhibition zones at 2.5% concentration is 4.7mm, 5% (6.83mm), 7.5% (10.2mm) and positive control (20.57mm). This means that the higher the concentration, the larger the diameter of the inhibition zone obtained. The conclusion in this study is bandotan leaf extract (Ageratum conyzoides L.) can be formulated into anti acne sheet mask which is stable during storage with a strong inhibitory power at 7.5% concentration, which is 10.2 mm.Keywords: Ageratum conyzoides L., bandotan leaf, Propionibacterium acnes, sheet mask